Hereditary ovalocytosis - molecular analysis of hereditary Southeast Asian Ovalocytosis (SAO) in Bangka, South Sumatra. - Suryono Yudha Patria, Suryono Yudha Patria (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Southeast Asian Ovalocytosis (SAO) is a hereditary asymptomatic hemolytic disease characterized by oval form erythrocytes. This morphology is rigid and related with resistency to several strains of malaria parasites. The underlying molecular genetic abnormalities include heterozygous state for mutant band 3 protein, a membrane anion transporters protein.Objectives: To characterize the SAO in Bangka, South Sumatra in molecular level, by analyzing the DNA genome of three generation family with polymerase chain reaction (PCR).Methods: The DNA genome extracted from dried blood filter paper was used as template PCR. A pair of primers was synthesized in accordance with exon 11 of band 3 gene. The PCR product was studied under UV after electrophoresis on EtBr stained 3% agarose gel.Results: Both mutant alleles showed as smaller band compared to normal allele in all 6 heterozygote SAO persons, but not in the normal 8 cases. Deletions were predicted removing nine amino acids of band 3 protein. The mutant protein was possibly carried by the ancestor from China.Conclusions: Hereditary ovalocytosis in Bangka, Sumatra Selatan was caused by specific mutation on band 3 gene which is common mutation occurred in SAO patients.Keywords: Bangka ovalocytosis - SAO - Band 3 protein - EPB3 gene deletion - PCR